Analysis of Teamwork, Organizational Culture, and Work Environment on Employee Job Satisfaction at PT Perkebunan Nusantara IV Regional I Medan - Izriyana; Abdi Setiawan; M. Chaerul Rizky (International Journal of Society and Law, 2024)
This study aims to find the influence of teamwork, organizational culture And work environment on employee job satisfaction PT Nusantara IV Plantation Region I Medan . The number of samples in this study was 65 respondents in the Human Resources and Management Systems section . This study used quantitative data processed with SPSS 25.0 with a multiple linear regression model. The results of the study showed that teamwork , organizational culture And work environment partially and simultaneously has a positive and significant effect on employee job satisfaction at PT Perkebunan Nusantara IV Regional I Medan . The results of the t-test show that teamwork has a regression value of 0.308, a calculated t value of 2.612 and a significance of 0.000. Organizational Culture has a regression value of 0.252, a calculated t value of 2.274 and a significance of 0.000. Work Environment has a regression value of 0.418 and a calculated t value of 3.461 . The results of the determination coefficient test of 89.4 % job satisfaction can be explained and obtained from the variables of teamwork, organizational culture And work environment while the remaining 10.6% is influenced by other factors.